Image Guided percutaneous pigtail catheter drainage of Liver Abscess technique and its outcome - Jain, Bhavika; Mantri, Nikita; Saraf, Rishika; Pole, Shivaji; Dahiphale, Devidas Baburao; Lahoti, Amol (Asian Journal of Medical Sciences, 2021)
Background: Liver abscesses are localized collections of necrotic inflammatory tissue caused by bacterial, parasitic or fungal agents. These abscesses are usually suspected clinically in cases having fever and tender hepatomegaly. The diagnosis is usually confirmed on the basis of imaging such as ultrasound and computerised tomography. Management includes antimicrobial agents and drainage of abscess. Percutaneous drainage of abscess is done using needle aspiration or catheter drainage. Aims and Objective: The main aim of the study was to evaluate the role of pigtail catheterization drainage procedure as a treatment option in cases of liver abscess. Materials and Methods: It was a prospective study conducted ata tertiary care medical college. Fifty patients having hepatic abscess were included in this study over a period of one year from August 2018 to September 2019 on the basis of a predefined inclusion and exclusion criteria. These patients underwent pigtail catheterization of liver abscess as a treatment. The demographic characteristics, hepatic lobe involvement, offending organisms and complications were studies in these patients. Results: Out of 50 patients 35 were male and 15 were femalewith a M: F ratio of 1:0.42. The age ranged from 4 years to 92 years. The mean age of the studied cases was found to be 38.64 +/- 18.17 years. Right lobe was involved in predominant cases. most common individual organism involved in hepatic abscess formation was klebsiella (30%) followed by streptococcus (20%) and E-coli (8%) organisms. Seven patients developed procedure related complications out of which 5 patients had catheter dislodgment requiring repositioning of catheter 1 patient developed pus discharge from catheter site and remaining 1 patient developed subcapsular hematoma. Conclusion: Percutaneous image guided pigtail catheter of liver abscess is an effective minimal procedure as a treatment option for liver abscess with high success rate with no mortality related to procedure.